The modern transformation and design research of fuyang paper cutting under the perspective of shape grammar - Li Bohao; Musnin Misdih (Universiti Teknologi MARA, 2024)
This paper investigates the modern transformation and application of Fuyang paper-cutting patterns to protect and promote the inheritance and development of Fuyang paper-cutting while also exploring effective ways to preserve it. This study employs qualitative analysis methods, including literature review and case studies. It combines the Shape Grammar (SG) theoretical model with computer-aided design technology to conduct an in-depth exploration and analysis of Fuyang paper-cutting patterns. As a result, related derivative pattern elements were generated and applied in relevant product designs. The research findings indicate that the derivative patterns of Fuyang paper-cutting generated using the "SG" theory model can be successfully applied in modern product design. It also effectively broadens the channels for disseminating Fuyang paper-cutting as intangible cultural heritage, providing valuable references and insights for the living inheritance and sustainable development of intangible cultural heritage.